INTRODUCTION INFORMATIVELY COMMUNICATIVE TECHNOLOGIES In EDUCATIONAL PROCESS of HIGHER EDUCATIONAL ESTABLISHMENT. - H. M. Gudyreva (Kherson State University, 2010)
The article is devoted to the questions of introduction informatively communication technologies in the educational process of higher educational establishment, in particular at teaching of higher mathematics. The place of ICT is examined in the educational process of higher educational establishment. The examples of the use are resulted informatively communication technologies in the educational process of higher educational establishment, in particular at teaching of higher mathematics.